Inflammation Disturbed the Tryptophan Catabolites in Hippocampus of Post-operative Fatigue Syndrome Rats via Indoleamine 2,3-Dioxygenas Enzyme and the Improvement Effect of Ginsenoside Rb1 - Liu, Shu; Cheng, Yue; Chen, Wei-Zhe; Lv, Jin-Xiao; Zheng, Bei-Shi; Huang, Dong-Dong; Xia, Xu-Fen; Yu, Zhen (Frontiers in Neuroscience, 2021)
Aim Post-operative fatigue syndrome (POFS) is a common complication that prolongs the recovery to normal function and activity after surgery. The aim of the present study was to explore the mechanism of central fatigue in POFS and the anti-fatigue effect of ginsenoside Rb1. Method We investigated the association between inflammation, indoleamine 2,3-dioxygenase (IDO) enzyme, and tryptophan metabolism in the hippocampus of POFS rats. A POFS rat model was induced by major small intestinal resection. Rats with major small intestinal resection were administered ginsenoside Rb1 (15 mg/kg) once a day from 3 days before surgery to the day of sacrifice, or with saline as corresponding controls. Fatigue was assessed with the open field test (OFT) and sucrose preference test (SPT). ELISA, RT-PCR, Western blot, immunofluorescence, and high-performance liquid chromatography (HPLC) were used to test the inflammatory cytokines; p38MAPK, NF-κB/p65, and IDO enzyme expressions; and the concentrations of tryptophan, kynurenine, and serotonin, respectively. Result Our results showed that POFS was associated with increased expressions of inflammatory cytokines and p38MAPK and higher concentrations of kynurenine and tryptophan on post-operative days 1 and 3; a lower serotonin level on post-operative day 1; and an enhanced translocation of NF-κB/p65 and the IDO enzyme on post-operative days 1, 3, and 5. Ginsenoside Rb1 had an improvement effect on these. Conclusion Inflammatory cytokines induced by large abdominal surgery disturb tryptophan metabolism to cause POFS through the activation of the p38MAPK–NF-κB/p65–IDO pathway in the hippocampus. Ginsenoside Rb1 had an anti-fatigue effect on POFS by reducing inflammation and IDO enzyme.